Pertimbangan Hakim Terhadap Pelaku Recidive Narkotika (Analisis Putusan Nomor 36/PID.SUS/2021/PN PSP) - Lubis, Rini Anggraini (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research was conducted in Padangsidimpuan City, precisely at the Padangsidimpuan City District Court, the problem in this study was the judge's consideration of narcotics recidive perpetrators. This type of research is field research, with a Juridical Empirical approach, there are two sources of data, primary data sources from judges and secondary data sources in the form of books, journals and others. Data collection techniques were carried out through interviews, documentation, then the data obtained from the results of research in the field or literature were analyzed using a qualitative descriptive analysis study. Based on the research, it was found that the aggravating sentence for the defendant in Decision Number 36/Pid.sus/2021/PN Psp, namely because the defendant's actions did not support the Government's program in eradicating narcotics trafficking, then the mitigating factors were that the defendant had already been convicted, the defendant was very sorry and will not repeat his actions. Narcotics crime in decision No. 36/Pid.Sus/PN Psp according to Islamic Criminal Law is threatened with Ta'zir punishment, as well as repetition of criminal acts as stated in Decision No. 36/Pid.Sus/2021/PN Psp without any weighting punishment if someone repeats the same act a second time, but if there is someone who repeats the crime up to 4 (four) times then the sanction is the death penalty. According to the author's analysis, the sentence for the defendant in Decision Number 36/Pid.Sus/2021/PN Psp should be someone who has been convicted according to the criminal procedure law, that is, the punishment is included in an aggravating matter, and according to Islamic criminal law if someone has been punished a second time, the punishment remains the same.